THE PORTRAYAL OF COMMODIFICATION PHENOMENON IN VLADIMIR NABOKOV’S NOVEL ENTITLED LOLITA - CARISA, AINESA ZANA (Jurnal Ilmiah Mahasiswa FIB, 2013)
This article analyzes the portrayal of commodification in human’s behavior as depicted a novel entitled Lolita. Such phenomenon could be found in the novel, in which the main character named Humbert Humbert is tend to behave in such way. Vladimir Nabokov as the author shows that human’s treatment towards each other can be affected by material point of view. The writer used Marxism approach in analyzing the depiction and applying theory of commodification and adding few social-economical references in order to reveal the depiction clearly. It will focus on Humbert Humbert characteristic as the basis of his commodification behavior then moved to his relationship with the characters in the novel that is related with commodification value. The result shows that Humbert’s relationship with some characters in the novel is proven to involves both sign and exchange value.   Keywords: Marxism, Commodification, Exchange Value, Sign-exchange Value